Performance assessment and transient optimization of air precooling in multi-stage solid desiccant air conditioning systems - Gadalla, Mohamed (2016)
Renewable energy is one of the most promising solutions to both energy and global warming crisis. Energy consumption can be minimized considerably by utilizing solar energy in air conditioning systems operation. One of the popular solar air conditioning technologies is desiccant air conditioning. Nonetheless, conventional desiccant air conditioning systems have a relatively low coefficient of performance (COP). In consequence, two-stage desiccant air-conditioning systems are proposed to improve desiccant air conditioning systems’ COP. Moreover, a recently commercialized cooling method named Maisotsenko cooling cycle which is capable of cooling air near to its dew point temperature is considered to be integrated within the proposed multi-stage desiccant cooling systems. In this paper, three new two-stage desiccant air conditioning systems incorporating Maisotsenko cooling cycle are proposed and investigated in details for hot and humid climates such as UAE. Furthermore, air precooling is considered to improve two stage desiccant air conditioning systems’ COP. Moreover, full transient analysis and optimization are carried out in UAE within June–October. The proposed system can minimize the required solar heating during noon time as the ambient air dry bulb temperature rises. Average COP of the system during electricity load peak hours (10:00–14:00) for all five considered and combined months is 1.77. Average rate of heat input required to operate the system and average building cooling load are determined to be 100.3 kW and 46.2 kW, respectively. Therefore, system average COP is computed to be 0.46.